Uso de internet y su influencia en el rendimiento académico de los estudiantes de décimo año de educación básica del Colegio Nacional Mixto Dr. José María Velasco Ibarra del cantón El Guabo, durante el periodo lectivo 2012-2013. - Quichimbo Quichimbo, René Guillermo (2013)
The use of the Internet, today strongly influences education either positively or negatively it involved concern among parents and teachers of the Joint Dr. José María Velasco Ibarra National College form, so work began research to establish a proposal for the welfare of the educational community, the conclusions they arrive determined that 60% acquired the use of the internet do so to conduct research.